Media cat Minyak dan Pendukungnya - Gozali, Amir (Institut Seni Indoensia Surakarta, 2010)
The artwork must not only be measured/ assessed from the outside impression of the observer but also the good and bad quality of the physical. It depens how the process works is made, for the quality of course work rwquired precision in the selection of good materials and application of proper techniques in making a painting. Media oil paint, began to be known/discovered in the 15th century (the time Renisance in Europe). This medium was found closely related to the spirit if the Renaissance itself is the rebirth of ideas, thoughts Ancient Greek and Roman times are based on human reason(rationalism) and values of humanity (humanism) and the view that humans are used as a source all actions. As a result of the industrial revolution had improved oil paints in term of shape as it begins to be mass produced. Form of oil paint which originally separate between base material and developed into oil and solids in the form of a paste-like tube packaging at this time with different brands and package sizes. This makes oil paint more and more popular today because it has the character of a flexible and practical in its use.Keywords : painting,medium,oil paint